EFEKTIVITAS REBUSAN DAUN SIRIH HIJAU TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI DESA MOJONGAPIT JOMBANG: The Effectiveness Of Green Betel Leaf Decoction Against Perineal Wound Healing In Postpartum Mothers In Mojongapit Village, Jombang - Kolifah; Dwi Srirahandayani; Ana Dyah Aliza; Ferry Ruslia K (LPPM - STIKES Pemkab Jombang, 2022)
Cases of infection during the puerperium are caused by infections that are localized in the birth canal and the most common cause, more than 50%, are anaerobic Streptococcus bacteria which are actually not pathogenic. Green betel leaves are known to have antiseptic and antibacterial properties. The research method is quasi-experimental, the population taken in this study was postpartum mothers who were in the village of Mojongapit, Jombang district, with a total of 24 respondents. The technique used in sampling is purposive sampling. The inclusion criteria for sampling were as follows: postpartum mothers who experienced second and third degree perineal injuries with physiological delivery, mothers who were willing to become respondents. Analysis using the Mann - Whitney Test. The results showed that the healing time for perineal wounds in postpartum mothers who were given boiled green betel leaves was 4 - 6 days. The length of time for perineal wound healing in postpartum women who were not given boiled green betel leaves was 5-9 days. Differences in the duration of perineal wound healing in postpartum women who were given green betel leaf decoction was 0.4 times faster than postpartum women who were not given green betel leaf decoction